Transcutaneous electrical nerve stimulation (TENS): A potential intervention for pain management in India? - Gourav Banerjee; Mark I Johnson (Indian Journal of Pain, 2013)
Globally, the burden of pain and consequent disability on healthcare and economy is significant. Given the pain prevalence, inconsistent, and inadequate specialist health care services in India, the burden is likely to be magnified. Analgesic medication is the mainstay treatment for most types of pain; however, its side effects and financial costs for prolonged periods of time have resulted in the search for safer, inexpensive treatment options. Transcutaneous Electrical Nerve Stimulation TENS is a non-invasive, self-administered and inexpensive analgesic technique used worldwide to manage pain. Evidence suggests that TENS is effective in relieving acute and chronic pain and can be used as a stand-alone treatment for mild to moderate pain or as an adjunct for moderate to severe pain. The purpose of this study is to overview the principles, techniques, and clinical research evidence when TENS is used to manage pain with reference to health care and research studies conducted in India. A summary of evidence was formed based on Cochrane reviews, systematic reviews and meta-analyses on TENS with respect to pain management.